Integration of a Two-Stage Preclinical and Clinical Diagnostic Algorithm for the Early Detection and Management of Echinococcal Disease - Butaboev , Jasurbek; Shaykhova , Guli; Qosimov , Adham (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
Epidemiological metrics indicate a persistently high regional prevalence of cystic echinococcosis, demanding targeted evaluations of early diagnostic frameworks. The current investigation analyzes the multidimensional dynamics of a novel two-stage preclinical and clinical diagnostic algorithm designed for the early detection of hepatic hydatidosis. The study population comprised 135 individuals residing in endemic zones, systematically monitored over a 36-month period utilizing a prospective cohort design. Empirical clinical data demonstrate a robust inverse correlation between the implementation of the two-stage protocol (combining high-sensitivity serological screening with targeted ultrasonographic volumetry) and the incidence of advanced-stage disease presentation. Analytical outputs confirm that this targeted profiling optimizes diagnostic accuracy, yielding a cumulative sensitivity of 94.8 percent and a specificity of 92.3 percent, compared to 76.5 percent diagnostic accuracy in the standard symptomatic observation cohort. The dynamics of the obtained results mandate an urgent paradigm shift from passive clinical observation toward active, biomarker-driven preclinical screening. Patients subjected to the novel algorithmic approach exhibited a significantly higher rate of early-stage (CE1 and CE2) detection (82.3 percent versus 35.8 percent) and a corresponding reduction in the necessity for radical surgical interventions. These findings bridge persistent literature gaps by validating a comprehensive diagnostic interaction model, establishing a rigorous foundation for future preventive strategies in clinical parasitology.